Knowledge of companion animals’ practitioners on stem-cell based therapies in a clinical context: a questionnaire-based survey in Portugal - Lopes, Rafael S.; Requicha, João; Carolino, Nuno; Costa, Eduardo; Carvalho, Pedro (BMC veterinary research, 2025)
Stem cells therapies are a promising therapeutic option, and although not yet widely used in daily clinical practice in companion animals, they have shown great potential in the treatment of a variety of diseases. This study aims to investigate the individual profile of Portuguese veterinary practitioners, their knowledge about this type of therapy and their interest in its future use and application. This questionnaire-based descriptive study was carried out in Portugal from November 2021 to January 2022. A questionnaire-based survey was conducted online, using an electronic platform. The following topics were surveyed: (i) profile of veterinarians; (ii) knowledge about cell therapies; and (iii) interest in future use and application. After an internal validation, the survey was released online for three months in Portuguese veterinary social network groups. Data were collected and descriptive analysis and Chi-square test were performed. A total of 275 responses were obtained and analysed. Analysis of the results showed that the participating veterinarians know what mesenchymal stromal cells (MSCs) are (90.9%) and are generally aware of their therapeutic potential (94.5%). Regarding their use, 56.7% of the respondents do not know their application in veterinary pathologies. The remaining 43.3% indicated the situations in which they knew of its use. Orthopaedic and dental or oral diseases were the most frequently mentioned. Regarding the immunological effect of MSCs, there is a great lack of information. Data analysis showed that 72.4% of respondents were unaware of the possibility of an immunogenic response following their administration. However, 53.5% stated that they were aware of the positive immunomodulatory capacity. Most professionals who participated in this survey consider this topic relevant in veterinary medicine (95.6%), as well as the existence of this type of service in the national territory (96.4%). The great interest shown by 96.7% of the respondents in learning more about the subject highlights the importance of raising awareness, conducting further studies and promoting knowledge sharing in their daily clinical practice and research. The relationship between the national status of stem-cell therapy and veterinarians’ knowledge is influenced by limited regulation but growing professional interest and driven by private companies and professional organisations. This study contributes to a better understanding of the trends related to this topic in the context of veterinary practice in Portugal.